Pengaruh Kepadatan Yang Berbeda Terhadap Kelulushidupan Dan Pertumbuhan Ikan Nila (Oreochromis niloticus) Pada Sistem Resirkulasi Dengan Filter Bioball - Alfia, Averus Rizki; Arini, Endang; Elfitasari, Tita (Journal of Aquaculture Management and Technology, 2013)
Aquaculture production process have started to use intensive systems, with high stocking density and minimum water usage. High density may become dangerous for the survival of fish, inhibits the growth of fish and water quality. This research was carried out to know the effect of different density on survival rates and growth of Tilapia (Oreochromis niloticus) in the recirculation system using bioball filter. This research was performed at the Laboratory of Fisheries building, Faculty of Fisheries and Marine Science, Diponegoro University, Semarang. And conducted for 42 days from August to October 2012. The research used 9 containers size 18 liters buckets, each bucket’s filled with 10 liters of water and flowed by filter bucket. Experimental fish was tilapia with an average initial weight of 2.9 g/fish. The research used completely randomized design with 3 treatment (density of 10, 15 and 20 fishes) and three replications. Feed used in the form of commercial feed given 3% of the biomass. The results showed that density has no significant effect on survival rate, but it shows a highly significant effect towards absolute gowth and specific gowth rate. Best density is 10 fishes with an average absolute gowth of 8.77 g, and the specific gowth rate of 3.268%/days. Use filters bioball for ammonia recirculation system can reduce the density of 20 fishes up to the sixth week of the experiment.